856 NODAL METASTASES AFTER NEOADJUVANT CHEMORADIATION AND R0 RESECTION IN ESOPHAGEAL ADENOCARCINOMA: PATTERNS AND PROGNOSIS. (17th September 2021) - Harrington, Caitlin; Carr, Rebecca; Sihag, Smita; Adusumilli, Prasad; Bains, Manjit; Bott, Matthew; Isbell, James; Park, Bernard; Rocco, Gaetano; Rusch, Valerie; Jones, David; Molena, Daniela
Abstract: : Although the pattern of nodal metastasis and the prognosis of number and location of positive nodes have been well described with esophageal cancer undergoing upfront surgery, little is known about nodal metastasis after neoadjuvant treatment. The aim of this study is to assess the pattern of nodal metastases in esophageal adenocarcinoma treated with neoadjuvant chemoradiation and surgery and evaluate its effect on prognosis. Methods: All patients with esophageal adenocarcinoma who had undergone neoadjuvant chemoradiation and an R0 esophagectomy between 2010 and 2018 at our institution were included (n = 577). Pathology reports were reviewed for sites of lymph node metastases. Patients were excluded if nodal stations were not listed separately (n = 40). Age, sex, race, tumor location, TRG, pT stage, number of positive lymph nodes, number of positive nodal stations, and specific nodal stations were analyzed for risk of recurrence using univariable Cox regression, and significant covariates were included in multivariable Cox regression model. Results: Of 537 patients, 193(36%) had pathologic nodal metastases. 153 patients(28%) had single-station disease: 135(88%) at the paraesophageal station, 16(10%) at the left gastric, 1 at the subcarinal and 1 at the paratracheal station(0.65% each). 32 patients(6.0%) had two-station and 8(1.5%) had three-station disease. The majority of patients with multiple positive nodal stations had positive nodes in the paraesophageal(90%) and/or left gastric artery stations(60%). On multivariable analysis, the number of positive nodal stations (HR 1.59, CI 1.35–1.84, p < 0.001), subcarinal (HR 2.78, CI 1.54–5.03, p < 0.001), and paraesophageal stations (HR 2.0, CI 1.58–2.54, p < 0.001) were associated with increased risk of recurrence. Conclusion: Patients who have undergone neoadjuvant and R0 esophagectomy for adenocarcinoma often have lymph node metastases at time of surgery, most commonly at the paraesophageal station. The number of nodal stations, along with subcarinal and paraesophageal metastases, were associated with increased risk of recurrence.